Bioelectromics of a photosynthetic microalgae assisted microbial fuel cell for wastewater treatment and value added production - Ankesh Ahirwar; Mohd Jahir Khan; Priyanka Khandelwal; Gurpreet Singh; Harish; Vandana Vinayak; Makarand Madhao Ghangrekar (Scientific Reports)
Abstract Power generation and recovery of value-added products using microalgae, Haematococcus lacustris is tested in a dual chamber photosynthetic microalgae-assisted microbial fuel cell (PMA-MFCt1). The microalgal cells in conical flask act as control. The performance was compared to another, test PMA-MFCt2. The control MFC in second test had electrode wires not connected (PMA-MFCnw). The PMA-MFCt1 set had microalgal catholytic media replenished unlike in PMA-MFCt2. A comparative PMA0-MFC, was used without microalgae and only water as catholyte. The results demonstrated maximum power density (PDmax) of 33.76 mW m−2 in PMA-MFCt1, 15.36 mW m−2 in PMA-MFCt2 and 8.05 mW m−2 in PMA0-MFC. The non replenishment of catholytic media in PMA-MFCt2 set resulted in nutrient limitations, poor photosynthesis, and disrupted redox reactions. Further lowest PDmax in PMA0-MFC proves that microalgae are excellent source of free nascent oxygen required for redox reaction. Taxonomic identity of microbes at the anode via 16 S rRNA showed the dominance of catalytic microbes mainly Proteobacteria. The different kinds of carotenoids from microalgae were estimated by UV-Vis and liquid chromatography-mass spectrometry (LC-MS) analysis. The microalgal growth, evaluated in terms of biomass dry weight (DW), was 118 mg L−1, after 40 days of PMA-MFCt1 operation, which was lesser than in control (conical flask) 123 mg L−1. The pigments including total chlorophyll (a + b), and total carotenoids were 699.7 µg g−1 and 224.6 µg g−1, respectively, on day 16. Microalgal performance in PMA-MFCt2 and its control (PMA-MFCnw) was 10% and 32.52% inferior than in PMA-MFCt1 and its control. The continuous replenishment of media in PMA-MFCt1 maintained microalgal cells in continuous state of multiplication and photosynthesis resulting into higher bioelectricity generation and bioproducts than PMA-MFCt2, and PMA-MFCnw.